A mobile application tool for standing posture analysis: development, validity, and reliability - AVCI, ENDER ERSİN; TİMURTAŞ, EREN; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (SPRINGER LONDON LTD, 2021)
Background Using mobile application for postural assessments has been drawing a rising interest due to widespread use of smartphones. Although there are some mobile applications in use, validated mobile tools for accurate postural assessment are still warranted. Aims This study aimed to develop Fizyoprint mobile application tool to assess standing posture and investigate the validity and reliability of the application in young adults. Methods A convenience sample of 20 young adults (12 men and 8 women with a mean age of 21.3 +/- 2.2 years) and 2 physiotherapists as raters participated in the study. The participant's digital images were obtained from the anterior, posterior, and right lateral sides. The raters selected the anatomic reference points by using digital markers in the app screen, and the Fizyoprint application, with Turkish language option, calculated a total of 26 posture variables, including 11 distance and 15 angle variables. Each participant was assessed twice (1-week interval) by 2 raters with Fizyoprint. Inter- and intra-rater reliabilities were estimated using the intraclass correlation coefficient. The BioTonix (TM) posture analysis system was used for validation. Results A total of 80.7% (21 variables) indicated acceptable to excellent intra-rater reliability results. A total of 57.7% (15 variables) were found to be acceptable to excellent for inter-rater measurements. The results confirmed the validity of the Fizyoprint application for testing the standing posture. Conclusions Fizyoprint application is a new, valid, free mobile tool with acceptable concordance with BioTonix (TM) postural analysis system for assessing standing posture. Further studies are warranted to test the current application in different populations and musculoskeletal conditions.
Keywords: Assessment; Mobile applications; Posture; Reliability; Validity; ADOLESCENTS; CHILDREN; IPHONE